PROJETO DE SALA DE AULA AUTOMATIZADA COM O USO DA INTERNET DAS COISAS E MQTT - Delfino, Lorrainy R.; Santos, Otávio Lube dos (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Smart environments connect with their devices and allow their interaction in order to collect information about their users and perform the commands they request. Monitoring and controlling the use of electrical and electronic equipment in these environments is important, given its maintenance costs and the consumption of electricity. This article presents the design of an automated classroom, aiming to improve the use of its users, by controlling the electronic devices of the classroom and the management of the hours of use. For that, an Internet of Things (IoT) interface was implemented with the MQTT protocol, keeping a channel open so that information can be accessed at any time since the system is connected to the Internet.